(untitled) (International Journal of Engineering and Computer Science, 2015)
The paper represents the various types of syntactic errors, their detection and further their correction system. This method of detection and correction of the syntactic errors is inspired by the need to correct them for a correct grammatical sentence formation. The best systems, however, results in syntactic errors due to of the lack of linguistic knowledge. An attempt to optimize the task of detecting and correcting the syntactic errors is reflected in this paper.